Discussion on Covid-19 and International Relations: VOSviewer Bibliometric Analysis of Articles by US and Chinese Authors - Yeyen Subandi; Ariel Nethan; Maria Veri Diana Baun Yuel (PT FORMOSA CENDEKIA GLOBAL, 2023)
The initial emergence of the coronavirus which made the Covid-19 Pandemic in Wuhan, China, made the international world of countries coordinate and cooperate with each other to deal with the pandemic. The Chinese government is accelerating in fighting the pandemic by providing medical assistance, cooperating with other countries, and actively promoting community-building with a shared future for humanity and the process of globalization. Different state policies in handling it make researchers determined to carry out research whose articles have been published by Scopus to become material for study and policy. This study aims to explain writing trends and characteristics of International Relations and Covid-19 conducted by authors from the United States and China. In this study using the VOSviewer bibliometric analysis method, a study conducted by researchers found that the trend of Scopus-indexed journal articles from authors in the United States and China had grown quite significantly until 2022.